Unravelling undergraduate mathematics students' understanding of derivatives - Aniswita, Aniswita; Sepriyanti, Nana; Medika, Gema Hista (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2024)
Derivatives are a significant concept in calculus; nonetheless, students' conceptual understanding remains inadequate. Therefore, a conceptual understanding of this subject should be a priority. This study aimed to elucidate the conceptual understanding of Mathematics Education students on the topic of Derivatives. A qualitative approach was employed. The participants in this study comprised 62 students enrolled in the Mathematics Education programme who completed the Differential Calculus course. The instrument employed was a conceptual knowledge assessment comprising three questions that examined the definitions of derivatives, derivative theorems, and derivatives of implicit functions. To investigate students' conceptual understanding, the researcher interviewed four students selected to represent each category for every topic. The employed data analysis method was qualitative data analysis as per Miles and Huberman. The findings indicated that the majority of students had not employed the correct notion. Students encounter difficulties in determining the differentiability of a function at a certain point and in applying the rules of multiplication and differentiation to implicit functions. It can be argued that students' conceptual understanding of derivatives was significantly deficient.